Trends in Pulmonary Embolism Deaths Among Young Adults Aged 25 to 44 Years in the United States, 1999 to 2019 - Zuin, Marco; Bikdeli, Behnood; Armero, Andre; Porio, Nicole; Rigatelli, Gianluca; Bilato, Claudio; Piazza, Gregory (The American journal of cardiology, 2023)
A concerning increase in mortality from acute pulmonary embolism (PE) in young adults in the United States has been reported. We extracted PE-related mortality rates (number of deaths per US population) from the Centers for Disease Control and Prevention Wide‐Ranging Online Data for Epidemiologic Research database from 1999 to 2019, focusing on subjects aged 25 to 44 years. Age‐adjusted mortality rates (AAMRs) were assessed using the Joinpoint regression modeling and expressed as the estimated average annual percentage change (AAPC) with relative 95% confidence intervals (95% CIs) and stratified by urbanization, gender, age, and race. Between 1999 and 2019, the AAMR from acute PE in US adults aged 25 to 44 years linearly increased without any difference between genders (AAPC +1.5%, 95% CI 1.2 to 1.8, p <0.001). AAMR increase was more pronounced in American-Indians/Alaska Natives and in Asian/Pacific Islanders (AAPC +2.5%, 95% CI 1.6 to 3.4, p <0.001), Whites (AAPC +1.7%, 95% CI 1.4 to 2.0, p <0.001), Latinx/Hispanic patients (AAPC +1.7%, 95% CI 0.6 to 3.0, p = 0.003), and residents of rural areas (AAPC +2.4%, 95% CI 1.9 to 2.8, p <0.001). A higher AAMR (4.02 per 100,000 residents, 95% CI 3.90 to 4.15) and absolute number of PE-related deaths were observed in the South. PE-related mortality in adults aged 25 to 44 years has increased over the last 2 decades in the United States. Stratification by race, ethnicity, urbanization, and census region showed ethnoracial and regional disparities that will require further evaluation and remedy.